Clinical symptoms related to patients with hyperinfection syndrome, infected with strongyloides stercoralis: Case series - Zahra Ahmadnia; Hossein Ghorbani; Arshiya Yahyazadeh Jolodar; Alireza Firouzjahi; Farzane Jafarian; Rouzbeh Mohammadi Abandasari; Masoumeh Bayani (Chronic Diseases Journal)
BACKGROUND: Strongyloides stercoralis (S. stercoralis) is endemic in the northern provinces of Iran, and to identify it, in addition to clinical tests, clinical manifestations of the patient are also needed. This study aimed to investigate the clinical manifestations of patients with S. stercoralis infection.